Optimization of Cementitious Wasteform for Immobilizing C-14 in CaCO3 Radioactive Waste - Hwang, Jaewoong; Kim, Hyung-Ju; Lee, Keunyoung; Sohn, Sungjune (Archives of Metallurgy and Materials, 2026)
This study examines the feasibility of immobilizing dispersive CaCO3 radioactive waste containing C-14 carbonate based on ordinary Portland cement (OPC) hydration. Cementitious wasteforms were fabricated by incorporating CaCO3 of waste loadings ranging from 20 to 60 wt.% by a conventional cement paste method. The performance of wasteform was evaluated in terms of mechanical and chemical durability specified in the waste acceptance criteria (WAC) for low- and intermediate-level radioactive waste disposal in the Republic of Korea. The compressive strength was evaluated under open and sealed curing conditions at curing periods of 7 and 28 days. As CaCO3 content increased, the compressive strength was generally reduced, however, maximum value was obtained under 30 wt.% CaCO3 with all curing conditions. Chemical durability was evaluated according to the ANSI/ANS-16.1 method. Linear cumulative leaching behavior of carbon was shown for all compositions. The leaching indices was derived with ranging of 12.0-12.7, corresponding to extremely low effective diffusion coefficients. Therefore, it was shown that OPC-based hydration provides an effective and acceptable immobilization strategy for dispersive CaCO3 radioactive waste.